A Calcium/Cation Exchanger Participates in the Programmed Cell Death and in vitro Virulence of Entamoeba histolytica - Valle-Solis, Martha; Bolaños, Jeni; Orozco, Esther; Huerta, Miriam; García-Rivera, Guillermina; Salas-Casas, Andrés; Chávez-Munguía, Bibiana; Rodríguez, Mario A. (Frontiers in Cellular and Infection Microbiology, 2018)
Entamoeba histolytica is the etiologic agent of human amoebiasis, disease that causes 40,000 to 100,000 deaths annually worldwide. The cytopathic activity as well as the growth and differentiation of this microorganism is dependent on both, extracellular and free cytoplasmic calcium. However, few is known about the proteins that regulate the calcium flux in this parasite. In many cells, the calcium extrusion from the cytosol is performed by plasma membrane Ca2+-ATPases and calcium/cation exchangers. The aim of this work was to identify a calcium/cation exchanger of E. histolytica and to analyze its possible role in some cellular processes triggered by calcium flux, such as the programmed cell death and in vitro virulence. By searching putative calcium/cation exchangers in the genome database of E. histolyica we identified a protein belonging to the CCX family (EhCCX). We generated a specific antibody against EhCCX, which showed that this protein was expressed in higher levels in E. histolytica than its orthologous in the non-pathogenic amoeba E. dispar. In addition, the expression of EhCCX was increased in trophozoites incubated with hydrogen peroxide. This E. histolytica exchanger was localized in the plasma membrane and in the membrane of some cytoplasmic vesicles. However, after 10 min of erythrophagocytosis, EhCCX was found predominantly in the plasma membrane of the trophozoites. On the other hand, the parasites that overexpress this exchanger contained higher cytosolic calcium levels than control, but the extrusion of calcium after the addition of hydrogen peroxide was more efficient in EhCCX-overexpressing trophozoites; consequently, the programmed cell death was retarded in these parasites. Interestingly, the overexpression of EhCCX increased the in vitro virulence of trophozoites. These results suggest that EhCCX plays important roles in the programmed cell death and in the in vitro virulence of E. histolytica.